Analysis Of The Influence Of Port Export And Import Volume On Economic Growth In North Sumatera And West Sumatera Provinces - Nuri Rahayu Ningsih; Andria Zulfa; Bakhtiar Efendi; Lia Nazliana Nasution; Rusiadi Rusiadi (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Using a quantitative approach, this study investigates the effect of port export and import volumes on economic growth in North Sumatra and West Sumatra Provinces. Time series data from the World Bank and the Central Statistics Agency (BPS) from 2006 to 2023 are used as secondary data. The analysis uses the ARDL Panel model, which allows for analysis of data dynamics across time and regions. The results show that the three main indicators that affect economic growth (GRDP) in both provinces, both in the short and long term, are export volume, inflation, and exchange rates. In North Sumatra, export volume has a positive impact on GRDP, while import volume has a negative impact, indicating a risk of dependence on imports. Controlled inflation also has a positive impact, while the exchange rate shows a diversion. Policy recommendations are expected to improve global competitiveness and exchange rate stability through coordination of fiscal and monetary policies, support for the Export Capacity Building Program and MSMEs through the Regional Comprehensive Economic Framework (RCEP), and export diversification to reduce dependence on certain commodities. This study emphasizes that policies that are responsive to changes in trade at the national to international levels are an important foundation for stabilizing sustainable economic growth.